Proceedings of the Fourth Workshop on Computer Modelling in Decision Making (CMDM 2019) 2019
DOI: 10.2991/ahcs.k.191206.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuroevolution Forecasting of the Living Standards of the Population

Abstract: The article is devoted to the problem of forecasting indicators of living standards using neuroevolutionary approach. The NEAT method is considered that allows generating the neural network topology automatically. The paper proposes modification of this method and its implementation based on the activation functions mutation, which enabled to expand the set of possible solutions. A comparative analysis of the training, testing, and forecasting accuracy is carried out. Target indicator forecasting was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In this study, using the Baikal region example, this method was tested and showed good results. Therefore, to forecast the eco-socio-economic development of the Baikal region, we chose artificial neural networks with automatic topology construction, particularly the forecasting method proposed in [27,28], and the software developed on its basis [30]. This forecasting technique is based on the use of a multilayer perceptron (MLP) [39] in combination with evolutionary calculations [40,41].…”
Section: Neural Network Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, using the Baikal region example, this method was tested and showed good results. Therefore, to forecast the eco-socio-economic development of the Baikal region, we chose artificial neural networks with automatic topology construction, particularly the forecasting method proposed in [27,28], and the software developed on its basis [30]. This forecasting technique is based on the use of a multilayer perceptron (MLP) [39] in combination with evolutionary calculations [40,41].…”
Section: Neural Network Methodsmentioning
confidence: 99%
“…In the forecasting methodology and the program [27,28,30], the neural network training algorithm was used using the NEAT method, which uses a genetic algorithm and automatically builds the neural network topology in the learning process [44]. This method trains neural networks for target indicators.…”
Section: Neural Network Methodsmentioning
confidence: 99%
See 1 more Smart Citation